Визначення оптимального матеріалу плит гасильного вагона - Нестеренко, Сергій Вікторович; Борисенко, Олександр Людвикович; Баннiков, Леонід Петрович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Деформація та руйнування футерувальних плит пода кузова гасильного вагона погіршує сходження коксу при вивантаженні, призводить до його зависання, вимагає зупинки вагона на обслуговування та ремонт. Встановлено, що пластини експеримен-тального поду менш схильні до процесів розтріскування під напругою в умовах мокрого гасіння коксу. За три місяці експлуатації на плитах експериментального поду не виявлено тріщин, на відміну від вихідного варіанту, де тріщини були зафіксовані в 10% пластин. Термін служби плит в 1,5 рази перевищує вихідний варіант. Таким чином, для підвищення стійкості плит гасильного вагона в умовах експлуатації можна розглянути використання корекції вмісту марганцю малосірчистого ударостійкого чавуну ЧХ-1, який не схильний до корозійного розтріскування під напругою в умовах мокрого гасіння. Це дозволить збільшити термін служби плит до 0,5 року. Deformation and destruction of the lining plates of the bottom of the body of the quenching car worsens the descent of coke during unloading, leads to its freezing, requires stopping the car formaintenance and repair. Deformation and damage of the lining plates of the quenching car’s body 51bottom worsen coke discharge during unloading, lead to coke hang-ups, and require stopping thecar for maintenance and repairs. It has been established that the plates of the experimental bottom are less susceptible to stress corrosion cracking under wet coke quenching conditions. Over three months of operation, no cracks were detected in the plates of the experimental bottom, in contrast tothe original design, where cracks were found in 10% of the plates. The service life of the plates is 1.5 times longer than that of the original design. Thus, to improve the durability of the quenching car plates under operating conditions, it is possible to consider adjusting the manganese content in low-sulfur impact-resistant cast iron ChKh-1, which is not prone to stress corrosion cracking underwet quenching conditions. This could increase the service life of the plates up to 0.5 years.
Keywords: гасіння коксу; легування марганцем; жаростійкий чавун; гасильний вагон; coke quenching; manganese alloying; heat-resistant cast iron; quenching car